Exceptional events classification in the portuguese quality of electricity supply regulation - Pousinho, Hugo (2018)
This paper addresses the concept of the classification of exceptional events (EE) introduced, in 2013, during the revision of the Portuguese quality of electricity supply code. An exceptional event is classified as such by the Portuguese national regulatory authority after a request from the network operator. The request must include a detailed description of the incident and the collected evidence, in order to prove that the four cumulative criteria for the classification as exceptional event are satisfied. The procedure for the classification of exceptional events was applied to requests submitted in 2014 by the main Portuguese distribution system operator.